Long-Term Physical Exercise and Mindfulness Practice in an Aging Population - Tang, Yi-Yuan; Fan, Yaxin; Lu, Qilin; Tan, Li-Hai; Tang, Rongxiang; Kaplan, Robert M.; Pinho, Marco C.; Thomas, Binu P.; Chen, Kewei; Friston, Karl J.; Reiman, Eric M. (Frontiers in Psychology, 2020)
Previous studies have shown that physical exercise and mindfulness meditation can both lead to improvement in physical and mental health. However, it is unclear whether these two forms of training share the same underlying mechanisms. We compared two groups of older adults with 10 years of mindfulness meditation (integrative body-mind training, IBMT) or physical exercise (PE) experience to compare their effects on brain, physiology and behavior. Fifty-five healthy older adults were randomly selected from a large community health project and the groups were compared on measures of quality of life, autonomic activity (heart rate, heart rate variability, skin conductance response, respiratory amplitude/rate), immune function (secretory Immunoglobulin A, sIgA), stress hormone (cortisol) and brain imaging (resting state functional connectivity, structural difference). In comparison with PE, we found significantly higher ratings for the IBMT group on dimensions of life quality. Parasympathetic activity indexed by skin conductance response and high-frequency heart rate variability also showed more favorable outcomes in the IBMT group. However, the PE group showed lower basal heart rate and greater chest respiratory amplitude. Basal sIgA level was significantly higher and cortisol concentration was lower in the IBMT group. Lastly, the IBMT group had stronger brain connectivity between the dorsal anterior cingulate cortex (dACC) and the striatum at resting state, as well as greater grey matter in the striatum. Our results indicate that mindfulness meditation and physical exercise function in part by different mechanisms, with PE producing greater physical fitness and IBMT inducing greater central nervous system changes. These findings suggest combining physical and mental training may achieve better health and quality of life for aging population.